Energy efficiency optimisation for SWIPT AF two‐way relay networks. Issue 6 (1st March 2017) - Zhou, Xiang; Li, Quanzhong
Abstract : A joint power splitting ratio optimisation and power allocation scheme is proposed to maximise the energy efficiency in amplify‐and‐forward two‐way relay networks with the simultaneous wireless information and power transfer scheme. Both the locally optimal solution and simplified equal power allocation scheme with closed‐form expressions are derived. Simulation results show the effectiveness of the proposed schemes.